Lack of effectiveness of adherence counselling in reversing virological failure among patients on long‐term antiretroviral therapy in rural Uganda. Issue 1 (21st August 2019) - Birungi, J; Cui, Z; Okoboi, S; Kapaata, A; Munderi, P; Mukajjanga, C; Nanfuka, M; Nyonyintono, MS; Kim, J; Zhu, J; Kaleebu, P; Moore, DM
Abstract : Objectives: The current World Health Organization and Uganda Ministry of Health HIV treatment guidelines recommend that asymptomatic patients who have a viral load (VL) ≥ 1000 HIV‐1 RNA copies/mL should receive adherence counselling and repeat VL testing before switching to second‐line therapy. We evaluated the effectiveness of this strategy in a large HIV treatment programme of The AIDS Support Organisation Jinja in Jinja, Uganda. Methods: We measured the HIV VL at enrolment, and for participants with VL ≥ 1000 copies/mL we informed them of their result, offered enhanced adherence counselling and repeated the VL measurement after 3 months. All blood samples with VL ≥ 1000 copies/mL were sequenced in the polymerase (pol) region, a 1257‐bp fragment spanning the protease and reverse transcriptase genes. Results: One thousand and ninety‐one participants were enrolled in the study; 74.7% were female and the median age was 44 years [interquartile range (IQR) 39–50 years]. The median time on antiretroviral therapy (ART) at enrolment was 6.75 years (IQR 5.3–7.6 years) and the median CD4 cell count was 494 cells/μL (IQR 351–691 cells/μL). A total of 113 participants (10.4%) had VLs ≥ 1000 copies/mL and were informed of the VL result and its implications and given adherence counselling. Of these 113 participants, 102 completed 3 months of follow‐up and 93 (91%) still had VLs ≥ 1000 copies/mL. We successfully genotyped HIV for 105 patients (93%) and found that 103 (98%) had at least one mutation: eight (7.6%) had only one mutation, 94 (89.5%) had two mutations and one sample (1%) had three mutations. Conclusions: In this study, enhanced adherence counselling was not effective in reversing virologically defined treatment failure for patients on long‐term ART who had not previously had a VL test.